(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Benign prostatic hyperplasia (BPH) is one of the most prevalent urological disorders affecting aging men and represents a significant global health burden due to its progressive nature and impact on quality of life. This condition is characterized by nonmalignant enlargement of the prostate gland, leading to lower urinary tract symptoms that range from mild discomfort to severe bladder outlet obstruction. The pathophysiology of BPH is multifactorial and involves age-related hormonal alterations, chronic inflammation, stromal–epithelial interactions, and dysregulation of growth factors. Clinically, BPH manifests through both storage and voiding symptoms, often necessitating long-term management. Advances in diagnostic approaches, including symptom scoring systems, imaging modalities, and functional urodynamic assessments, have improved early detection and disease stratification. Contemporary management strategies encompass conservative monitoring, pharmacological therapy, minimally invasive interventions, and surgical techniques tailored to disease severity and patient-specific factors. The selection of optimal treatment requires a comprehensive evaluation of symptom burden, prostate volume, comorbidities, and patient preferences. This review aims to provide an integrated overview of the epidemiology, underlying mechanisms, clinical presentation, and current evidence-based management of benign prostatic hyperplasia. Emphasis is placed on recent therapeutic advancements and personalized treatment approaches that contribute to improved clinical outcomes and enhanced quality of life for affected patients.